The effect of local aspiration and methotrexate injection on live interstitial pregnancy coexisting with live intrauterine pregnancy after assisted reproductive technology. Issue 7 (22nd April 2019) - Yang, Xinyun; Zhu, Linling; Le, Fang; Wang, Yanjing; Lou, Hangying; Gao, Huijuan; Zhu, Yimin; Jin, Fan
Abstract: Aim: To share the experience of local aspiration and instillation of methotrexate (MTX) to selective reduction of live interstitial pregnancy and to evaluate its clinical effect and the outcome of intrauterine pregnancy. Methods: Twelve patients with heterotopic interstitial pregnancy were enrolled at Women's Hospital, Zhejiang University School of Medicine, from 2006 to 2017. All the pregnancies were derived from assisted reproductive technology (ART). The transvaginal aspiration to interstitial pregnancy sac and local instillation of MTX (range from 12.5 to 30 mg) were performed for the patients under ultrasound‐guide. The prognosis and pregnancy outcomes were followed up. Results: No severe side effects of medical treatment were observed in all patients. Three cases underwent subsequent laparotomy cornual resection, and no perioperative complications were found in these three patients. Twelve patients gave birth to 13 healthy infants without congenital anomalies. The average birth weight and gestational age was 2837 g (SD ± 605 g) and 36.8 weeks (SD ± 2.4 weeks). No growth anomalies and mental retardation were observed in live birth offspring. Conclusion: The transvaginal ultrasound‐guided aspiration and injection of MTX might be a feasible alternative treatment for heterotopic interstitial pregnancy when vital signs of patients are stable.